PEMBERIAN HADIAH DAN HUKUMAN UNTUK MENINGKATKAN HASIL BELAJAR PKn KELAS VI SDN 020 LANGSAT HULU KECAMATAN BENAI KABUPATEN KUANTAN SINGINGI - Rostina Rostina (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
Research on giving rewards and punishment to improve learning outcomes civics Class VI SDN 020 Langsat Hulu Subdistrict of Kuantan Singingi Regency is aimed to improve learning outcomes of civics students grade VI SDN 020 Langsat Hulu with gift and punishment in the learning process. The study was conducted on 30 students consisting of 13 male students and 17 female students. Data obtained through teacher observation sheet, student activity (punishment and reward) with observer grade teacher of SDN 020 Langsat Hulu. The test results are given at the end of the lesson by using formative tests then the data is analyzed with descriptive statistics. The results showed that the results of learning civics grade VI students have increased. This result can be seen based on the value of learning outcomes that initially average tilapia 62 after being given gift gift modaling and punishment to 71, as well as student activity that has increased from treatment I to treatment II. This shows that the method of learning with reward and punishment can improve the learning outcomes of civics students of class VI SDN 020.